954; An International Multi-Centre Appraisal of The Management of Acute CHOLEcystitis During The COVID-19 Pandemic: The CHOLECOVID Study - Spiers, H V M (British journal of surgery, 2021)
Aim National guidance issued in response to COVID-19 resulted in adoption of non-surgical modes of treatment in emergency surgery, including acute cholecystitis (AC). The aim of the CHOLECOVID Study is to understand the changes in management and outcomes of AC during COVID19, since becoming the definitive global study on the subject. Method Patients >18 years admitted to hospital with radiologically confirmed AC, during two predefined 8-week time periods: P1 (pre-pandemic) 12/09/19-12/11/19; P2 (during the pandemic) 12/03/20-12/05/20, were included. The primary outcome was 30-day all-cause mortality. Secondary outcomes included severity of AC, radiological diagnostic modalities implemented, definitive management and pulmonary complications. Results 9,615 patients were included from 39 countries (P1:5,381; P2:4,234). 30-day mortality was higher in P2 (1.7%vs2.4%;p<0.015). Higher rates of moderate and severe AC were seen in P2 (30.1%vs35.1%;3.7%vs4.1%). First-line CT imaging was more common in P2 (36.3%vs46.3%;p<0.001). There were higher failure rates of conservative management in P2 (37.4% vs 44.4%; P < 0.001). Cholecystostomy rates were higher in P2 (5.8%vs8.8%;P<0.001). Overall, 4.6% (n = 193) of P2 patients were COVID-19 positive, with overall mortality of 0.7% (n = 30). There was no significant difference in pulmonary complications between COVID-19 positive or negative patients. Conclusions During the COVID-19 pandemic, a small increase in mortality among AC patients was noted, when compared to the pre-pandemic cohort. Patients during the COVID-19 pandemic presented with more severe AC, resulting in altered trends in diagnosis and management. New guidance and clear pathways are required to safely manage AC moving forward, in the face of further waves of COVID-19.